Comparative research on ＂high currents＂ induced by single event latch-up and transient-induced latch-up - 陈睿 韩建伟 郑汉生 余永涛 上官士鹏 封国强 马英起 (Chinese physics B, 2015)
By using the pulsed laser single event effect facility and electro-static discharge （ESD） test system, the characteristics of the ＂high current＂, relation with external stimulus and relevance to impacted modes of single event latch-up （SEL） and transient-induced latch-up （TLU） are studied, respectively, for a 12-bit complementary metal--oxide semiconductor （CMOS） analog-to-digital converter. Furthermore, the sameness and difference in physical mechanism between ＂high current＂ induced by SEL and that by TLU are disclosed in this paper. The results show that the minority carrier diffusion in the PNPN structure of the CMOS device which initiates the active parasitic NPN and PNP transistors is the common reason for the ＂high current＂ induced by SEL and for that by TLU, However, for SEL, the minority carder diffusion is induced by the ionizing radiation, and an underdamped sinusoidal voltage on the supply node （the ground node） is the cause of the minority carrier diffusion for TLU.